Conceptual design exploration of a new aircraft passenger seat's tray table with adjustable height - Hafidh Said, Al Baalawy Said; Salim, Salim Mkubwa; Romli, Fairuz Izzuddin (The Aeronautical and Astronautical Society of the Republic of China, 2025)
Flight comfort has become an essential consideration among the aircraft passengers. One of the aspects that can contribute towards better passengers’ comfort during flight is the ease for them to conduct their in-flight activities. Since most of passengers’ in-flight activities involve the use of the seat tray table and each passenger has different body anthropometry, it is believed that the height of the seat tray table has a significant influence to the provision of ease and comfort for the passengers to conduct these activities. This notion is first demonstrated through conducted comfort experiment in an aircraft cabin mock-up. Based on the experimental results, it has been shown that different passengers will need different height of seat tray table to comfortably do their common in-flight activities. It is taken that these results support the need for a new seat tray table design that comes with an adjustable height feature. With this in mind, few alternative designs for a new seat tray table that is equipped with adjustable height feature have been developed and evaluated. Out of the three shortlisted design concepts, Design Concept 1 has been finally selected and it has been shown to be able to satisfy all outlined design requirements.